The march from early life food sensitization to allergic disease: a systematic review and meta‐analyses of birth cohort studies. Issue 1 (4th November 2015) - Alduraywish, S. A.; Lodge, C. J.; Campbell, B.; Allen, K. J.; Erbas, B.; Lowe, A. J.; Dharmage, S. C.
Abstract: Background: There is growing evidence for an increase in food allergies. The question of whether early life food sensitization, a primary step in food allergies, leads to other allergic disease is a controversial but important issue. Birth cohorts are an ideal design to answer this question. Objectives: We aimed to systematically investigate and meta‐analyse the evidence for associations between early food sensitization and allergic disease in birth cohorts. Methods: MEDLINE and SCOPUS databases were searched for birth cohorts that have investigated the association between food sensitization in the first 2 years and subsequent wheeze/asthma, eczema and/or allergic rhinitis. We performed meta‐analyses using random‐effects models to obtain pooled estimates, stratified by age group. Results: The search yielded fifteen original articles representing thirteen cohorts. Early life food sensitization was associated with an increased risk of infantile eczema, childhood wheeze/asthma, eczema and allergic rhinitis and young adult asthma. Meta‐analyses demonstrated that early life food sensitization is related to an increased risk of wheeze/asthma (pooled OR 2.9; 95% CI 2.0–4.0), eczema (pooled OR 2.7; 95% CI 1.7–4.4) and allergic rhinitis (pooled OR 3.1; 95% CI 1.9–4.9) from 4 to 8 years. Conclusion: Food sensitization in the first 2 years of life can identify children at high risk of subsequent allergic disease who may benefit from early life preventive strategies. However, due to potential residual confounding in the majority of studies combined with lack of follow‐up into adolescence and adulthood, further research is needed.